Analisa Pengendalian Internal Persediaan PT Riau Real Ranch Pekanbaru - Febdwi Suryani (COSTING : Journal of Economic, Business and Accounting, 2019)
Control activities are the policies and procedures that are owned by management to provide assurance that management has done as it should. This research was conducted at PT. Riau Real Ranch Pekanbaru with the aim of analyzing internal control of merchandise inventory. This analysis was conducted descriptively and used a sign test with data collection techniques for interviews, observations, and questionnaires. Based on the results of the study, overall internal control over merchandise inventory has been running effectively, this is indicated in the components of the control environment, risk assessment, control activities, and information and communication that have been significant. Conclusion, internal control over merchandise inventory has run effectively. Keywords: Analysis, Internal Control, Inventory